Hands-on Energy Adaptation Toolkit - World Bank (Washington, DC, 2014)
Hands-on Energy Adaptation Toolkit (HEAT) is an online resource that is designed to lead you through an assessment of climate vulnerabilities and adaptation options in your country's energy sector and raise awareness among key stakeholders. HEAT provides an interactive, step-by-step guide, as well as an analytical framework and support tools, to help policymakers consult with stakeholder groups to scope out climate risks and vulnerabilities. It then provides guidance on developing and selecting among options to manage, monitor, and evaluate these risks. HEAT provides guidance on how to complete the assessment process and explains the skills and expertise required in the team leading the assessment-the assignment management team. To ensure credibility when engaging stakeholders at various stages, the assignment management team should include experts with knowledge of the country's energy sector, energy asset performance, the effects of climatic and hydrological conditions on energy services, expertise in cost-benefit analysis, and skills in delivering participatory assessments. HEAT identifies key direct risks to energy supply and demand, and options for managing these risks. It also identifies additional research needed to better understand the implications of extreme climatic events for the energy sector as well as potential indirect impacts-for example, possible adaptation actions in the agriculture sector may affect energy supply.